2018
DOI: 10.1016/j.jtho.2018.08.1003
|View full text |Cite
|
Sign up to set email alerts
|

P1.16-34 The Impact of Pathology, Staging and Operative Resection on Survival and CT Evidence of Recurrence of Early NSCLC

Abstract: 672 VATS lobectomies were performed for the primary treatment of clinical stage I and II NSCLC, 43 patients with ground glass opacity or complex cases were excluded. Patients were analyzed according to ports used (one or multiple), R status, lobe-specific lymphadenectomy, subcarinal lymphadenectomy, length of hospital stay and length of thoracic drainage. A propensity-matched analysis was planned however, all variables were evenly distributed in both groups. Result: Of 629 VATS lobectomies, 234 (37%) were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…An important indicator of successful operation in radical surgery for lung cancer is the hilar mediastinal lymphadenectomy. Effective removal of the hilar and mediastinal lymph nodes during surgery can not only provide reference for postoperative pathological staging, but also affect the prognosis of patients (21,22). The results of Chang et al (23) showed that the total number of single utility port or double-port VATS lymph node dissection was similar.…”
Section: Discussionmentioning
confidence: 99%
“…An important indicator of successful operation in radical surgery for lung cancer is the hilar mediastinal lymphadenectomy. Effective removal of the hilar and mediastinal lymph nodes during surgery can not only provide reference for postoperative pathological staging, but also affect the prognosis of patients (21,22). The results of Chang et al (23) showed that the total number of single utility port or double-port VATS lymph node dissection was similar.…”
Section: Discussionmentioning
confidence: 99%